Acinetobacter meningitis in post neurosurgical patients: epidemiology, antimicrobial resistance, treatment options and risk factors that predict the outcome. - Bhargava, Aradhana; Mishra, Bibhabati; Thakur, Archana; Dogra, Vinita; Loomba, Poonam; Jain, Manisha; Gupta, Sonal; Banerjee, Priyanka; Haider, Mehvash (Canadian Journal of Infection Control / Revue Canadienne de Prévention des Infections)
Introduction: Post-operative meningitis caused by Acinetobacter sp. though a rare occurrence is a serious complication in neurosurgical ICUs. These are opportunistic organisms implicated in hospital-acquired infections. Aim: The aim was to study the epidemiology, the resistance pattern and the risk factors associated with the mortality in patients of post-operative Acinetobacter meningitis. Setting and design: Tertiary-care hospital and an observational study. Materials and methods: All patients with nosocomial post surgical meningitis due to Acinetobacter sp. between January 2008 and February 2010 were reviewed. Statistical analysis: It was performed by using Statistical Package for Social Sciences for Windows 12.0 Programme. Results: During the study period, 286 (8.71%) cases of post-operative meningitis were identified. (Total no. operated cases were 3283). Out of these 31 (10.84%) developed Acinetobacter baumannii meningitis. The mortality rates were 51.61% (16 patients). The risk factors which predict fatal outcome were underlying serious neurosurgical condition, presence of EVD and CVC, type and number of neurosurgical procedures, inappropriate antibiotic therapy, resistance to carbapenems, low Glasgow Coma score and inability to achieve sterilization of CSF. Most of the Acinetobacter strains were multi-drug resistant.